The hypertensive disorders of pregnancy : report of a WHO study group, meeting held in Geneva from 24 to 30 September 1985 - WHO Study Group on the Hypertensive Disorders of Pregnancy; World Health Organization (Geneva : World Health Organization, 1987)
An expert review of available epidemiological and clinical data that can be used to improve the classification, diagnosis, and management of the hypertensive disorders of pregnancy. In view of the complexity of these disorders and the frequency of conflicting evidence reported in the literature, the book makes a special effort to clarify controversies and to replace confusion with clear guidelines for diagnosis and treatment. More than 350 studies were critically evaluated. The book opens with a definition and classification of the clinical manifestations of these disorders, including explanations of the diagnostic significance of oedema, weight gain, blood pressure changes, and proteinuria. Other sections cover incidence, predisposing factors, patho-physiology, differential diagnosis, and treatment.
1. Introduction -- 2. The definition and classification of hypertensive disorders of pregnancy -- 3. The incidence of hypertensive disorders of pregnancy -- 4. Predisposing factors for hypertensive disorders of pregnancy -- 5. Pathophysiological aspects of hypertensive disorders of pregnancy -- 6. Diagnostic tests -- 7. Maternal complications of hypertensive disorders of pregnancy -- 8. Fetal and neonatal complications of the hypertensive disorders of pregnancy -- 9. Differential diagnosis of hypertensive disorders of pregnancy -- 10. The managements of hypertensive disorders of pregnancy : early case detection and primary health care -- 11. Treatment and management of hypertensive disorders of pregnancy in secondary and tertiary health care centres -- 12. Conclusions and recommendations -- References
Keywords: Pre-Eclampsia; Health of Special Groups